Role Of Economic Sectors In Bali On Economic Growth Of West And East Nusa Tenggara - Abyan Rai; Fizza Anindhita (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2020)
Bali is a province that has significant economic strength in various sectors. Bali has proximity to the West Nusa Tenggara and East Nusa Tenggara Provinces, and financial interaction can occur. This study analyzes the spillover effect of the Balinese economy on West Nusa Tenggara and East Nusa Tenggara. It looks at the West Nusa Tenggara and East Nusa Tenggara economies' response when the Bali economic sector experiences a shock. The method used is VECM using quarterly real GRDP data of 35 observations. This study found a positive relationship between the service sector and the Bali industry in West Nusa Tenggara's economic growth. The Balinese industrial sector also has a positive relationship with East Nusa Tenggara's economic growth. The spillover effect did not occur between the Bali industrial sector in general and the development of West Nusa Tenggara and the Bali service sector in general and East Nusa Tenggara's economic growth. The Balinese economy, which has a spillover effect on West Nusa Tenggara and East Nusa Tenggara's economic growth in several sectors, can be used as a reference for the government to make economic development policies.